Data for 'Robust estimation of quantitative perfusion using multi-phase pseudo-continuous arterial spin labelling' - Msayib, Y (University of Oxford, 2019)
NB: This is Version 2 of the data; Version 1 is at 10.5287/bodleian:6qq68o8oz. Microsoft Excel file containing the data tables corresponding to figures in this study. Not included are the example whole-brain images.